THE ROLE OF PARENTS IN LEARNING ABILITY WITH HYBRID LEARNING METHOD IN THE SEMI-URBAN COMMUNITY OF SIDOARJO - Rizky Aida Rachmayanti; Budi Haryanto (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2021)
The role of parents when mentoring children's learning must be considered, especially in current learning, by combining two learning methods between face-to-face and online, which is called a hybrid learning method. Parents must participate because, here, learning cannot be carried out optimally, and learning methods during the COVID-19 pandemic cannot be 100% applied by professional educators. This study aimed to obtain information about the role of parents in learning aqidah morals with the hybrid learning method in the semi-urban community of Sidoarjo. The research method used is interviews and documentation. This study describes the role of parents in learning moral aqidah divided into four stages: 1) controlling, 2) facilitator, 3) motivator, 4) evaluator. The role of parents is still minimal in terms of facilitators. Her parents only provide facilities to children in the form of data packages or WI-FI, cellphones, and so on, but parents prioritize cellphones when accompanying children's learning activities.